The lotus eaters - Macdonald, Marianne (London : William Heinemann, 2006)
Patty is in love with being in love. Strikingly beautiful, she knows the impact she has on men. She falls for one after another of Lottie's male friends, destroying relationships and marriages. Eventually Patty manages to destroy even her friendship with Lottie and with everyone else she has ever been close to.
Keywords: Contemporary -- fiction; Domestic fiction